A year in the South : - Ash, Stephan V. (Palgrave Macmillan, 2002)
A Year in the South is about four ordinary people in an extraordinary time. They lived in the South during 1865 -- a year that saw war, disunion, and slavery give way to peace, reconstruction, and emancipation. One was a slave determined to gain freedom, one a widow battling poverty and despair, one a man of God and planter’s son grappling with spiritual and worldly troubles, and one a former Confederate soldier seeking a new life. Between January and December 1865 they witnessed, from very different vantage points, the death of the Old South and the birth of the New South. Civil War historian Stephen V. Ash reconstructs their daily lives, their fears and hopes, and their frustrations and triumphs in vivid detail, telling a dramatic story of real people in a time of great upheaval and offering a fresh perspective on a pivotal moment in history.